Mechanisms of Immune Evasion in Chronic Hepatitis B Infection: The Role of Cytokines and Immune Cells - Kadhim, Maytham Khazaal; K. Kanani, Ekhlas A.; Abdulqader, Noora Khudhur (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Chronic hepatitis B (CHB) affects approximately 296 million people globally, causing significant liver fibrosis and cancer. CHB is characterized by immune dysfunction, including impaired innate responses, defective intercellular signaling, and exhausted T/NK cells regulated via PD-1/PD-L1 checkpoints. The precise link between cytokine dysregulation and cellular exhaustion within the human liver remains poorly understood. Objective: To investigate CHB immune evasion mechanisms through computational analysis of published human liver datasets, examining relationships between immune recognition, antigen presentation, checkpoint pathway activation, and cytokine environments including IL-10, TGF-β, and IFN-α/γ in shaping T/NK cell functional states across disease progression. Methods: Liver biopsy data from CHB patients across three datasets (GSE84044, GSE83898, GSE230397; n=120) underwent normalization and immune deconvolution using CIBERSORTx and EPIC. Differential expression, gene set enrichment, checkpoint interactions, and cytokine signaling were quantified alongside known HBV immune evasion mechanisms including RIG-I/MDA5 inhibition and HBsAg/HBeAg-mediated suppression. Results: CHB livers showed attenuated antiviral responses with reduced ISG expression, elevated IL-10/TGF-β, and altered Kupffer/monocyte phenotypes. Enhanced PD-L1 on liver and myeloid cells interacted with exhausted T/NK populations via PD-1, LAG-3, and CD94, with reduced cytotoxic CD8+ effectors and expansion of tolerogenic Tregs. HBx and polymerase-mediated PD-L1 upregulation were identified as central dysfunction drivers. Conclusions: CHB immune escape involves a self-reinforcing cycle where viral antigens suppress immunosurveillance and promote IL-10/TGF-β-dominated immunopathology, sustaining T/NK exhaustion. Biomarkers including PD-L1, IL10/TGFB1 modules, and the CD94/HLA-E axis may stratify patients and guide combination immunotherapies targeting checkpoint blockade alongside cytokine pathway modulation.